Pergesaran Kebiasaan Mengaji Pada Usia Remaja dari Tahun 1990-2016 di Kecamatan Ciwandan Kota Cilegon - faizudin faiz (Prodi Pendidikan Agama Islam STIT Al-Khairiyah Cilegon, 2021)
The Koran after Maghrib became a very beautiful sight in ancient times. The children enthusiastically came to the ustad's house to learn the Koran. Learning the Koran is an obligation that must be done by children in the past. After sunset, the chanting of the holy verses of the Qur'an was also faintly heard from people's homes. However, this culture seems to be fading day by day. Slumped with a very sharp angle of inclination. understand religion that is found at the empirical level or religion that appears in a formal form that is symptomatic in society. The practice of religion in the community is processed by its adherents from religious sources, namely the revelation of reasoning. For example, reading the book of fiqh, then fiqh which is the executor of the texts of the Qur'an and Hadith already involves elements of reasoning and human abilities.Factors that affect the shift in the Koran in the Ciwandan sub-district of CilegonCity include internal factors: Laziness, Prestige with younger children, Presence, School workload, Feeling that they can and external: Pragmatism of parents, Trans-Village to City Areas, Lack of motivation from people Parents or Relatives, Television Shows or the Presence of Electronic Media.